Public Knowledge and Attitude toward Crimean Congo Hemorrhagic Fever in Tokat Turkey - R Yilmaz; M Ozcetin; U Erkorkmaz; S Ozer; F Ekici (Tehran University of Medical Sciences, 2009)
Background: The World health Organization (WHO) declares Crimean Congo hemorrhagic fever (CCHF) endemic in Turkey. Despite the magnitude of problem, no documented evidence exists in Turkey, which reveals the awareness and practices of the country's adult population regarding CCHF, its spread, symptoms, treatment, and prevention. This study was conducted to assess the level of knowledge, attitudes, and practices regarding CCHF in people visiting tertiary care hospital in Tokat, Turkey. Methods: This questionnaire based cross-sectional survey was conducted among patients' relatives or guardians who admitted pediatric outpatient clinics during May-July 2008. The questionnaire was composed of 25 questions. Results: A total of 1034 respondents participated in the survey. Sufficient knowledge about CCHF was not found in 28.9% of the sample. Literate individuals were relatively better informed about CCHF as compared to the illiterate people. Television and radio were considered as the most important and useful source of information on the disease. Conclusion: We have found insufficient knowledge on CCHF in our population. It is thought to have no chance of success against a fatal disease such as CCHF, which has serious consequences, without the contribution of community. It is clear that there are important tasks for health, agriculture, and media sectors to improve public knowledge and awareness about CCHF.